Which young people in England are most at risk of an alcohol-related revolving-door readmission career?. (December 2017) - Hoy, Andrew
Abstract Background This research investigated what Hospital Episode Statistics (HES) records could reveal about the development of problematic drinking careers among young people in England. Methods A cohort of 7286 young people (aged 12-18) who had an index alcohol-related emergency admission between April 2003 and March 2004 were investigated for subsequent alcohol-related readmission. Regressions of patient and visit characteristics were performed against measures of readmission. Results A total of 677 patients (9.3% of the cohort) were readmitted during the following 3.75 years, and this group had on average 1.52 readmissions following their index admission. Predictors of having a first readmission included living in a deprived area at index admission (B = -.081, OR = .923, 95% CI = .894 to .952, df = 1, p  < .001); having another substance use diagnosis (B = .302, OR = 1.352, 95% CI = 1.017 to 1.798, df = 1, p < .05), or a comorbid mental health diagnosis (B = .441, OR = 1.555, 95% CI = 1.147 to 2.108, df = 1, p  < .01), or a diagnosis of self-harm (B = .316, OR = 1.371, 95% CI = 1.082 to 1.738, df = 1, p  < .01) at index admission. These last three results were also associated with the readmission rate being higher for young women than young men (B = -.250, OR = .779, 95% CI = .656 to .925, df = 1, p  < .01). Patients who had an injury diagnosis alongside their alcohol diagnosis were less likely to be readmitted in the future (B = -.439, OR = .645, 95% CI = .475 to .876, df = 1, p  < .01) On average, each subsequent admission featured a longer hospital stay; was progressively more likely to occur on a non-traditional drinking day; and occurred after a progressively smaller number of days since previous admission. Conclusions This study illustrates ways in which problematic drinking careers can be analysed using routinely collected health information, and the results from this analysis may be useful in informing the process of hospital screening and treatment referral. The effects of poverty and comorbid conditions on the initiation of a drinking career are suggested by these results.